Analysis of freezing and thawing processes in clay with freeze-induced compression (FIC) model - Satoshi Nishimura; Mingxuan Liang; Chuangxin Lyu (Soils and Foundations)
Fine-grained soils generally exhibit significant permanent compression due to freezing and thawing cycles. The nature of this compression was explored through the numerical analysis of two series of freezing (and thawing) experiments involving a wide range of temperature gradients (0.04–5 °C/mm) performed under K0 conditions. A submodel that describes a state-dependent plastic volumetric strain rate during freezing and thawing, originally developed by Nishimura (2021), was employed for the fully Thermo-Hydro-Mechanically (THM) coupled Finite Element (FE) analysis. The submodel, called the Freeze-Induced Compression (FIC) module, works as an add-in to any elasto-plastic frozen soil model developed under a THM framework, and can be turned on or off according to the need. The elasto-plastic model for frozen/unfrozen states was reappraised and re-formulated such that all parameter values could be determined from conventional frozen/unfrozen tests. This paper illustrates the model/module implementation, as well as its effectiveness in describing both slow frost heave tests and fast repeated freeze–thaw cyclic tests. In the latter, the analysis with and without the FIC module indicated that macroscopic, inter-element water transfer alone plays only a secondary role in causing cumulative permanent volumetric strain. This insight highlights the need to implement an explicit module to describe freeze-induced compression, as is done in the present study.